Механізми захисту віртуального середовища - Шульга, М. Д. (ХНУРЕ, 2023)
As the adoption of virtualization technologies continues to expand, so do the threats to information security, leading to heightened focus on protective measures. Virtual infrastructure is becoming increasingly reliable and capable of addressing a broad spectrum of security issues. However, the primary challenges concerning virtualization platform security lie in the design o f the final solutions based on them. It is evident that deploying a virtual infrastructure presents distinct security challenges, such as hypervisor vulnerabilities, virtual machine (VM) isolation, and configuration errors. Identifying and mitigating these risks contribute to preserving the confidentiality, integrity, and availability of an organization's data and IT resources.